An Analysis of Teachers’ Teaching Style in Teaching Writing Skills at SMA Negeri 2 Banjarmasin - Aprilliani, Nia; Kamal, Sirajuddin; Mu'in, Fatchul (EduCurio: Education Curiosity, 2025)
This study aims to analyze teachers' teaching style to teach English writing skills to students in grades XI and XII at SMA Negeri 2 Banjarmasin. Writing skills are crucial to English language learning in senior high schools in Indonesia. The research method was a descriptive qualitative method that utilized observation and interviews as the primary instruments. The research participants are English teachers in grades XI and XII at SMA Negeri 2 Banjarmasin. The results indicate that teachers' dominant teaching styles in teaching English writing at SMAN 2 Banjarmasin are formal authority and facilitator. Formal authority involves the teacher having complete control of the learning process, while the facilitator involves the teacher acting as a facilitator to help students acquire knowledge and skills independently. Formal authority and facilitator are two teaching styles to develop English writing skills in educational settings. This research provides an overview of the teaching approaches used in these settings. The findings have implications for improving the effectiveness of teaching English writing skills at the high school level.